A Characterization of Ultrasonic Full Angle Spatial Compounding as a Possible Alternative for Breast Cancer Screening - Luis MEDINA; Jorge CAMACHO; Carlos FRITSCH (Archives of Acoustics)
Breast cancer screening is based on X-ray mammography, while ultrasound is considered a complementary technique with improved detection in dense tissue. However, breast cancer screening requires a technique that provides repeatable results at the inspection interval which cannot be achieved with manual breast exploration.